Measures of the Glottal Source Spectrum. - Kreiman, Jody; Gerratt, Bruce R.; Antoñanzas-Barroso, Norma (Journal of Speech, Language & Hearing Research, 2007)
Purpose: Many researchers have studied the acoustics, physiology, and perceptual characteristics of the voice source, but despite significant attention, it remains unclear which aspects of the source should be quantified and how measurements should be made. In this study, the authors examined the relationships among a number of existing measures of the glottal source spectrum, along with the association of these measures to overall spectral shapes and to glottal pulse shapes, to determine which measures of the source best capture information about the shapes of glottal pulses and glottal source spectra. Method: Seventy-eight different measures of source spectral shapes were made on the voices of 70 speakers. Principal components analysis was applied to measurement data, and the resulting factors were compared with factors similarly derived from oral speech spectra and glottal pulses. Results: Results revealed high levels of duplication and overlap among existing measures of source spectral slope. Further, existing measures were not well aligned with patterns of spectral variability. In particular, existing spectral measures do not appear to model the higher frequency parts of the source spectrum adequately. Conclusion: The failure of existing measures to adequately quantify spectral variability may explain why results of studies examining the perceptual importance of spectral slope have not produced consistent results. Because variability in the speech signal is often perceptually salient, these results suggest that most existing measures of source spectral slope are unlikely to be good predictors of voice quality. Reprinted by permission of the publisher.